The Primary School in the Principality of Bulgaria (1878–1885) - Georgieva-Teneva, Ognyana (Poznańskie Studia Slawistyczne, 2024)
This research is based on the belief that the memory of spiritual development is part of contemporary culture. The subject of the paper is discussed in a diachronic plan: first the movement for education that began at the end of the XVIII century and passed through the stages of the cell, mutual and secular class schools during the Ottoman rule, is presented; and then the steps taken by the Bulgarian state restored in 1878 to build institutional primary education are traced. It is argued that the efforts towards mass literacy were part of the policy to modernize Bulgarian society and to stabilize sovereign Bulgaria. The research concludes that from being a privilege for a few, education is gradually becoming accessible to all and is seen as a pledge to consolidate society around universally shared educational values.